P-007 Aspects, large vessel occlusion, and time of symptom onset: estimation of eligibility for endovascular therapy. (23rd July 2017) - Mokin, M; Pendurthi, A; Ljubimov, V; Burgin, W; Siddiqui, A; Levy, E; Primiani, C
Abstract : Background and purpose: Understanding how many patients are eligible for endovascular therapy can help develop more effective stroke systems of care to improve delivery of endovascular therapy. Methods: In this single center retrospective cohort study we identified patients with acute ischemic stroke from LVO from January 2014 to December 2015. Selection criteria including LVO location, ASPECTS range, hospital arrival time and the use of intravenous thrombolysis were applied to calculate proportions of patients eligible for endovascular therapy. Results: Of 989 patients with acute ischemic stroke, LVO was identified in 224 (23%) of cases. 84% of patients admitted within 6 hours, 75% of patients admitted within 6–12 hours, and 77% of patients with M1 and ICA occlusions admitted within 12–24 hours had favorable ASPECTS for thrombectomy, defined as ASPECTS≥6. Severity of NIHSS was predictive of favorable ASPECTS (OR 0.20, 95% CI 0.04–0.74; p=0.014 for NIHSS>10 and OR 0.30, 95% CI 0.12–0.80; p=0.014 for NIHSS>20), whereas time of hospital arrival was not (OR 1.73, 95% CI 0.76–4.03; p=0.26). When all Class I, Level of Evidence A American Heart Association guidelines criteria were applied, 4% of patients with acute ischemic stroke were eligible for endovascular therapy. Up to 20% of patients were eligible for endovascular therapy when less restrictive criteria from Class IIb; Level of Evidence C were used instead. Conclusions: Depending on the sets of selection criteria, between 4% (the most restrictive criteria) and 20% (the least restrictive criteria) of patients with LVO are potentially eligible for endovascular therapy. Disclosures: M. Mokin: None. A. Pendurthi: None. V. Ljubimov: None. W. Burgin: None. A. Siddiqui: 1; C; NIH/NINDS/NIBIB, University at Buffalo. 2; C; Codman and Shurtleff, Inc., Concentric Medical, ev3/Covidien Vascular Therapies, GuidePoint Global Consulting, Penumbra, Stryker, Pulsar Vascular, MicroVention, Lazarus Effect, Blockade Medical. 3; C; Codman and Shurtleff, Inc. 4; C; Hotspur, Intratech Medical, StimSox, Valor Medical, Blockade Medical, and Lazarus Effect. 6; C; Abbott Vascular, Codman and Shurtleff, Penumbra Inc. E. Levy: 1; C; Covidien US SWIFT PRIME Trial. 2; C; Pulsar, Medina Medical, Blockade Medical. 4; C; Intratech Medical Ltd., Blockade Medical LLC, Medina Medical. 6; C; Abbott. C. Primiani: None.